Nano-catalyst as well as preparation method and application thereof

The Fe-Si-B-based alloy doped with transition metals forms a nanosheet-like porous structure, which solves the problem of insufficient electrocatalytic activity and stability of NS-Fe75Si12.5B12.5, and achieves efficient hydrolyzed hydrogen evolution reaction performance and industrial application.

CN120485815AActive Publication Date: 2025-08-15LIAONING UNIVERSITY OF TECHNOLOGY
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510833972.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-20
Publication Date
2025-08-15
Estimated Expiration
2045-06-20

AI Technical Summary

Technical Problem

The existing NS-Fe75Si12.5B12.5 has low electrocatalytic activity and stability, which is difficult to meet actual needs. The self-supporting performance of hydrothermal synthesis catalysts based on nickel foam substrates is insufficient, which restricts its industrial application potential.

Method used

The Fe-Si-B-based alloy with doped transition metal is used, and the chemical formula is Fe75-xMxSi12.5B12.5. M is selected from Co or Ni. It is formed by arc smelting and dealloyment corrosion treatment to form a nanosheet-like porous structure, which significantly increases the specific surface area and active sites.

Benefits of technology

It improves catalytic activity and stability, reduces the hydrogen evolution overpotential, optimizes the Tafel slope and charge transfer resistance, is suitable for large-scale production, and has better performance than precious metal-based catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120485815A_ABST
    Figure CN120485815A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of nano composite catalyst preparation, in particular to a nano catalyst and a preparation method and application thereof. The invention relates to a nano catalyst, which is a Fe-Si-B-based alloy doped with transition metal, and the chemical general formula of the nano catalyst is Fe < 75-x > M < x > Si < 12.5 > B < 12.5 >, x is 2 to 10; wherein M is selected from transition metal Co or Ni. According to the nano catalyst prepared by the preparation method disclosed by the invention, the problems that the electrocatalytic activity and the stability of NS-Fe75Si12.5 B12.5 are relatively low are solved. In addition, the preparation method is simple in process, high in repeatability and free of dependence on a foamed nickel substrate, and the nano-catalyst is excellent in self-supporting performance and suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of nanocomposite catalyst preparation, and in particular to a nanocatalyst and a preparation method and application thereof. Background Art

[0002] Element doping is an important research area in electrocatalysis. While precious metals (such as Pt) are currently considered the most active catalysts for the hydrogen evolution reaction (HER), their high cost and scarcity hinder their widespread application. To overcome this challenge, researchers are attempting to enhance catalyst performance by doping with other elements.

[0003] However, existing NS-Fe 75 Si 12.5 B 12.5 The electrocatalytic activity and stability of the catalyst are low, making it difficult to meet practical needs. The hydrothermal synthesis catalyst based on nickel foam substrate has insufficient self-supporting performance, which restricts its potential for industrial application. Summary of the Invention

[0004] In view of the shortcomings of the prior art, the present invention provides a nanocatalyst and its preparation method and application. The present invention provides a nanocatalyst which is a Fe-Si-B based alloy doped with transition metals, and its general chemical formula is Fe 75- x M x Si 12.5 B 12.5 , and x is 2 to 10; wherein M is selected from transition metals Co or Ni. The nanocatalyst of the present invention has a high specific surface area, a porous structure and excellent electrocatalytic performance, which overcomes the problems of the prior art NS-Fe 75 Si 12.5 B 12.5 The electrocatalytic activity and stability of the nanocatalyst are low, making it difficult to meet practical needs. In addition, the nanocatalyst of the present invention has excellent self-supporting performance and is suitable for large-scale production.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is: The first object of the present invention is to provide a nanocatalyst, wherein the nanocatalyst is a Fe-Si-B based alloy doped with a transition metal, and the general chemical formula thereof is Fe 75-x M x Si 12.5 B 12.5 ; x is 2 to 10; wherein, M is selected from transition metal Co or Ni, and X represents the atomic ratio of Co or Ni.

[0006] Preferably, the surface of the nanocatalyst is in a lamellar structure, the depth of the lamellar structure is nanometer-sized, and the lamellar structure has a high specific surface area and can expose more active sites.

[0007] Preferably, when M is a transition metal Co, the nanocatalyst is Fe 73 Co2Si 12.5 B 12.5 、Fe 70 Co5Si 12.5 B 12.5 、Fe 67 Co8Si 12.5 B 12.5 or Fe 65 Co 10 Si 12.5 B 12.5 .

[0008] Preferably, when M is transition metal Ni, the nanocatalyst is Fe 73 Ni2Si 12.5 B 12.5 、Fe 70 Ni5Si 12.5 B 12.5 、Fe 67 Ni8Si 12.5 B 12.5 or Fe 65 Ni 10 Si 12.5 B 12.5 .

[0009] A second object of the present invention is to provide a method for preparing the above-mentioned nanocatalyst, comprising the following steps: S1, according to the chemical formula Fe 75-x M x Si 12.5 B 12.5 , M is a transition metal Co or Ni, FeB, FeSi, pure Fe, Co or Ni are weighed and mixed to obtain a mixture; wherein x is 2 to 10.

[0010] S2. Smelting the mixture to obtain a Fe-Si-B based alloy doped with a transition metal.

[0011] S3. The Fe-Si-B based alloy doped with transition metal is subjected to dealloying corrosion treatment to corrode away Si atoms and part of B atoms on the surface of the Fe-Si-B based alloy doped with transition metal, so that the surface presents a lamellar structure, and the alloy is cleaned and dried to obtain a nanocatalyst.

[0012] Preferably, the conditions for the dealloying corrosion treatment are: corrosion in a 0.5 mol / L to 4 mol / L strong alkaline solution for 2 h to 3 h.

[0013] Preferably, the strong alkaline solution is selected from KOH solution or NaOH solution.

[0014] Preferably, the smelting treatment conditions are: smelting at 1800° C. to 2200° C. for 5 min to 10 min.

[0015] The third object of the present invention is to provide the use of the above-mentioned nanocatalyst in the preparation of a catalyst for hydrogen evolution by electrolysis of water.

[0016] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention provides a nanocatalyst, which is a Fe-Si-B based alloy doped with a transition metal, and its general chemical formula is Fe 75-x M x Si 12.5 B 12.5 , and x is 2 to 10; wherein M is selected from the transition metals Co or Ni. The nanocatalyst of the present invention restructures the electronic structure of the Fe-Si-B alloy through Co or Ni doping. Simultaneously, the nanosheet-like porous structure formed by the dealloying corrosion treatment significantly increases the specific surface area, exposing more active sites and synergistically improving catalytic activity and stability. This overcomes the low electrocatalytic activity and stability of pure FeSiB in the prior art, which makes it difficult to meet practical needs.

[0017] 2. The present invention provides a method for preparing a nanocatalyst having a general chemical formula of Fe 75-x M x Si 12.5 B 12.5 , M is a transition metal Co or Ni, FeB, FeSi and Fe, as well as Co or Ni are weighed and mixed to obtain a mixture; wherein x is 2 to 10; the mixture is smelted to obtain a Fe-Si-B based alloy doped with a transition metal; the Fe-Si-B based alloy doped with a transition metal is subjected to a dealloying corrosion treatment to corrode away Si atoms and part of B atoms on the surface of the Fe-Si-B based alloy doped with a transition metal, so that the surface presents a lamellar structure, and the nanocatalyst is obtained after cleaning and drying. The present invention adopts an arc melting method combined with a dealloying corrosion treatment, avoiding the complicated process of the traditional hydrothermal method or the molten salt method. The preparation method of the present invention is simple in process and highly repeatable, does not need to rely on a foamed nickel substrate, and the obtained nanocatalyst has excellent self-supporting performance and is suitable for large-scale production.

[0018] 3. The nanocatalyst of the present invention is used to carry out the electrolysis of water and hydrogen evolution reaction. Compared with Fe 75 Si 12.5 B 12.5 and NS-Fe 75 Si 12.5 B 12.5The Co or Ni doped nanocatalyst provided by the present invention has a 2 The hydrogen evolution overpotential under current density was reduced to 175.1mV and 168mV respectively (≥214mV for undoped system), the Tafel slope was significantly optimized to 134mV / dec and 158mV / dec (≥210mV / dec for undoped system), the charge transfer resistance of the optimal Co-doped nanocatalyst was as low as 2.265Ω, and the charge transfer resistance of the optimal Ni-doped nanocatalyst was as low as 2.515Ω (3.67Ω for undoped system). At the same time, the introduction of nanosheet-like porous structure significantly increased the electrochemical active surface area of the nanocatalyst of the present invention, and at 50mA / cm 2 The nanocatalyst of the present invention can operate stably for 15 to 20 hours under the current density, and the synergistic optimization of the active site density and electron transfer efficiency significantly enhances the kinetics and durability of hydrogen evolution in water electrolysis of the nanocatalyst of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 Fe of Example 4 65 Co 10 Si 12.5 B 12.5 and NS-Fe 65 Co 10 Si 12.5 B 12.5 And the Fe of Comparative Example 1 75 Si 12.5 B 12.5 XRD pattern of .

[0020] Figure 2 Fe of Example 4 65 Co 10 Si 12.5 B 12.5 and NS-Fe 65 Co 10 Si 12.5 B 12.5 Scanning electron microscope image and EDS spectrum of Fe 65 Co 10 Si 12.5 B 12.5 Magnified 5000 times, b is NS-Fe 65 Co 10 Si 12.5 B 12.5 Magnified 5000 times, c is NS-Fe 65 Co 10 Si 12.5 B 12.5 Magnified 7000 times, d is NS-Fe 65 Co 10Si 12.5 B 12.5 EDS spectrum.

[0021] Figure 3 Fe of Comparative Example 1 75 Si 12.5 B 12.5 EDS energy spectrum of , where (a) is a scanning electron microscope image, (b) is the EDS energy spectrum of Fe, and (c) is the EDS energy spectrum of B.

[0022] Figure 4 NS-Fe of Example 4 65 Co 10 Si 12.5 B 12.5 X-ray photoelectron spectrum of NS-Fe 65 Co 10 Si 12.5 B 12.5 , b is Co 2p, c is Fe 2p, d is Si 2p, and e is O 1s.

[0023] Figure 5 The nanocatalysts of Examples 1 to 4 and the NS-Fe of Comparative Example 1 75 Si 12.5 B 12.5 Electrocatalytic performance test diagram, wherein a is the LSV comparison diagram of the nanocatalysts of Examples 1 to 4, and b is the LSV comparison diagram of the nanocatalyst of Example 4 and the NS-Fe of Comparative Example 1. 75 Si 12.5 B 12.5 LSV comparison diagram, c is the overpotential diagram, d is the Tafel slope diagram, e is the impedance diagram, and f is C dl Figure 1 is a locally enlarged view of the potential range of -0.1V~-0.4V in Figure 1, and Figure 2 is a locally enlarged AC impedance spectrum of the high frequency region in Figure 1.

[0024] Figure 6 NS-Fe of Example 4 65 Co 10 Si 12.5 B 12.5 Stability test diagram, where a is a comparison of the linear sweep voltammetry characteristic curves before and after 1000 cyclic voltammetry cycles, and b is a curve of current density changing with time at a potential of 269 mV.

[0025] Figure 7 Fe of Example 5 73 Ni2Si 12.5 B 12.5 and Fe of Comparative Example 1 75Si 12.5 B 12.5 X-ray diffraction pattern of .

[0026] Figure 8 Fe of Comparative Example 1 75 Si 12.5 B 12.5 and NS-Fe of Example 5 73 Ni2Si 12.5 B 12.5 Scanning electron microscope image of Fe 75 Si 12.5 B 12.5 5000 times larger, b is NS-Fe in Example 5 73 Ni2Si 12.5 B 12.5 Magnified 5000 times, c is NS-Fe in Example 5 73 Ni2Si 12.5 B 12.5 Magnified 2000 times, d is the NS-Fe of Example 5 73 Ni2Si 12.5 B 12.5 Magnified 10000 times, e is NS-Fe in Example 5 73 Ni2Si 12.5 B 12.5 Magnified 20,000 times, f is NS-Fe of Example 5 73 Ni2Si 12.5 B 12.5 EDS spectrum.

[0027] Figure 9 NS-Fe of Example 5 73 Ni2Si 12.5 B 12.5 X-ray photoelectron spectrum of NS-Fe 73 Ni2Si 12.5 B 12.5 , b is Ni 2p, c is Fe 2p, d is Si 2p, and e is O 1s.

[0028] Figure 10 The nanocatalysts of Examples 5 to 8 and the NS-Fe of Comparative Example 1 75 Si 12.5 B 12.5 Electrocatalytic performance test diagram, wherein a is the LSV comparison diagram of the nanocatalysts of Examples 5 to 8, and b is the LSV comparison diagram of the Fe 73 Ni2Si 12.5 B 12.5 and NS-Fe 73 Ni2Si12.5 B 12.5 And the Fe of Comparative Example 1 75 Si 12.5 B 12.5 and NS-Fe 75 Si 12.5 B 12.5 LSV comparison diagram, c is the overpotential diagram, d is the Tafel slope diagram, e is the impedance diagram, g is the local magnification of the high frequency area in Figure e, and f is C dl picture.

[0029] Figure 11 NS-Fe of Example 5 73 Ni2Si 12.5 B 12.5 And the NS-Fe of Comparative Example 1 75 Si 12.5 B 12.5 Stability test diagram, wherein a is the NS-Fe of Example 5 73 Ni2Si 12.5 B 12.5 And the NS-Fe of Comparative Example 1 75 Si 12.5 B 12.5 LSV diagram after long cycle test stabilization, b is the NS-Fe of Example 5 73 Ni2Si 12.5 B 12.5 it picture. DETAILED DESCRIPTION

[0030] The following will clearly and completely describe the technical solution of the present invention in conjunction with the data in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0031] It should be noted that the professional terms used in the present invention are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specified, the various raw materials, reagents, instruments and equipment used in the following embodiments of the present invention can be purchased from the market or prepared by existing methods.

[0032] Currently, the existing NS-Fe 75 Si 12.5 B 12.5 The electrocatalytic activity and stability of the catalyst are low, making it difficult to meet practical needs. The hydrothermal synthesis catalyst based on nickel foam substrate has insufficient self-supporting performance, which restricts its potential for industrial application.

[0033] In view of the problems existing in the above-mentioned prior art, the present invention provides a nanocatalyst, which is a Fe-Si-B based alloy doped with transition metals, and its chemical formula is Fe 75-x M x Si 12.5 B 12.5 , and x is 2 to 10; wherein M is selected from transition metals Co or Ni.

[0034] The present invention reconstructs the electronic structure of the Fe-Si-B alloy by doping with Co or Ni. At the same time, the nanosheet layered porous structure formed by the dealloying corrosion treatment significantly increases the specific surface area, exposes more active sites, and synergistically improves the catalytic activity and stability, overcoming the problem that the existing technology of pure FeSiB has low electrocatalytic activity and stability and is difficult to meet actual needs.

[0035] The present invention utilizes an arc melting method combined with a dealloying corrosion treatment, avoiding the complex processes of traditional hydrothermal or molten salt methods. By regulating melting parameters and corrosion conditions, precise control of the nanocatalyst composition and structure is achieved. The preparation method of the present invention is simple, highly reproducible, and does not rely on a nickel foam substrate. The resulting nanocatalyst exhibits excellent self-supporting properties, making it suitable for large-scale production.

[0036] The nano catalyst prepared by the present invention has better performance than noble metal-based catalysts, overcomes the use of noble metals such as platinum in the preparation of hydrogen evolution reaction catalysts by electrolysis of water in the prior art, and reduces costs.

[0037] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below with reference to specific embodiments: Example 1 A method for preparing a nanocatalyst comprises the following steps: S1, according to the chemical formula Fe 75-x Co x Si 12.5 B 12.5 FeB, FeSi, pure Fe and Co were weighed, where x was 2; that is, according to the atomic ratio of Fe, B, Si and Co being 73:12.5:12.5:2, FeB (of which B accounted for 19.37%), FeSi (of which Si accounted for 75%), pure Fe and Co were weighed respectively, with a total mass of 20 g, and mixed to obtain a mixture.

[0038] S2. Place the mixture into an arc melting furnace and introduce argon gas into the furnace to create a protective atmosphere. Use arc discharge to generate high temperature to melt the mixture, and use magnetic stirring to fully mix the mixture. During the melting process, the front and back sides of the mixture are repeatedly melted three times, and each melting is accompanied by three magnetic stirring operations; after the melting is completed, the molten raw material is made into a φ6 cylindrical rod shape by arc melting and suction casting, and then naturally cooled to room temperature to obtain a Fe-Si-B based alloy doped with transition metals, which is recorded as Fe 73 Co2Si 12.5 B 12.5 .

[0039] S3. The cooled Fe-Si-B alloy doped with transition metals was cut using a wire cutting machine to obtain small iron pieces with a thickness of 0.5 mm and a length and width of 5 mm. The pieces were then placed in a 2 mol / L KOH solution and subjected to dealloying corrosion treatment for 3 h to obtain a nanocatalyst, designated as NS-Fe 73 Co2Si 12.5 B 12.5 .

[0040] Example 2 A method for preparing a nanocatalyst is the same as the method for preparing a nanocatalyst in Example 1, except that x in S1 is replaced by 5 from 2, and comprises the following steps: S1, according to the chemical formula Fe 75-x Co x Si 12.5 B 12.5 FeB, FeSi, pure Fe and Co were weighed, where x was 5; that is, according to the atomic ratio of Fe, B, Si and Co being 70:12.5:12.5:5, FeB (of which B accounted for 19.37%), FeSi (of which Si accounted for 75%), pure Fe and Co were weighed respectively, with a total mass of 20 g, and mixed to obtain a mixture.

[0041] S2. Place the mixture into an arc melting furnace and introduce argon gas into the furnace to create a protective atmosphere. Use arc discharge to generate high temperature to melt the mixture, and use magnetic stirring to fully mix the mixture. During the melting process, the front and back sides of the mixture are repeatedly melted three times, and each melting is accompanied by three magnetic stirring operations; after the melting is completed, the molten raw material is made into a φ6 cylindrical rod shape by arc melting and suction casting, and then naturally cooled to room temperature to obtain a Fe-Si-B based alloy doped with transition metals, which is recorded as Fe 70 Co5Si 12.5 B 12.5 .

[0042] S3. The cooled Fe-Si-B alloy doped with transition metals was cut using a wire cutting machine to obtain small iron pieces with a thickness of 0.5 mm and a length and width of 5 mm. The pieces were then placed in a 2 mol / L KOH solution and subjected to dealloying corrosion treatment for 3 h to obtain a nanocatalyst, designated as NS-Fe 70 Co5Si 12.5 B 12.5 .

[0043] Example 3 A method for preparing a nanocatalyst is the same as the method of Example 1, except that x in S1 is replaced by 8 from 2, comprising the following steps: S1, according to the chemical formula Fe 75-x Co x Si 12.5 B 12.5 FeB, FeSi, pure Fe and Co were weighed, where x was 8; that is, according to the atomic ratio of Fe, B, Si and Co being 67:12.5:12.5:8, FeB (of which B accounted for 19.37%), FeSi (of which Si accounted for 75%), pure Fe and Co were weighed respectively, with a total mass of 20 g, and mixed to obtain a mixture.

[0044] S2. Place the mixture into an arc melting furnace and introduce argon gas into the furnace to create a protective atmosphere. Use arc discharge to generate high temperature to melt the mixture, and use magnetic stirring to fully mix the mixture. During the melting process, the front and back sides of the mixture are repeatedly melted three times, and each melting is accompanied by three magnetic stirring operations; after the melting is completed, the molten raw material is made into a φ6 cylindrical rod shape by arc melting and suction casting, and then naturally cooled to room temperature to obtain a Fe-Si-B based alloy doped with transition metals, which is recorded as Fe 67 Co8Si 12.5 B 12.5 .

[0045] S3. The cooled Fe-Si-B alloy doped with transition metals was cut using a wire cutting machine to obtain small iron pieces with a thickness of 0.5 mm and a length and width of 5 mm. The pieces were then placed in a 2 mol / L KOH solution and subjected to dealloying corrosion treatment for 3 h to obtain a nanocatalyst, designated as NS-Fe 67 Co8Si 12.5 B 12.5 .

[0046] Example 4 A method for preparing a nanocatalyst is the same as the method for preparing a nanocatalyst in Example 1, except that x in S1 is replaced by 10 from 2, and comprises the following steps: S1, according to the chemical formula Fe75-x Co x Si 12.5 B 12.5 FeB, FeSi, pure Fe and Co were weighed, where x was 10; that is, according to the atomic ratio of Fe, B, Si and Co being 65:12.5:12.5:10, FeB (of which B accounts for 19.37%), FeSi (of which Si accounts for 75%), pure Fe and Co were weighed respectively, with a total mass of 20 g, and mixed to obtain a mixture.

[0047] S2. Place the mixture into an arc melting furnace and introduce argon gas into the furnace to create a protective atmosphere. Use arc discharge to generate high temperature to melt the mixture, and use magnetic stirring to fully mix the mixture. During the melting process, the front and back sides of the mixture are repeatedly melted three times, and each melting is accompanied by three magnetic stirring operations; after the melting is completed, the molten raw material is made into a φ6 cylindrical rod shape by arc melting and suction casting, and then naturally cooled to room temperature to obtain a Fe-Si-B based alloy doped with transition metals, which is recorded as Fe 65 Co 10 Si 12.5 B 12.5 . .

[0048] S3. The cooled Fe-Si-B alloy doped with transition metals was cut using a wire cutting machine to obtain small iron pieces with a thickness of 0.5 mm and a length and width of 5 mm. The pieces were then placed in a 2 mol / L KOH solution and subjected to dealloying corrosion treatment for 3 h to obtain a nanocatalyst, designated as NS-Fe 65 Co 10 Si 12.5 B 12.5 .

[0049] Example 5 A method for preparing a nanocatalyst is the same as the method of Example 1, except that the Co atoms in S1 are replaced by Ni atoms, comprising the following steps: S1, according to the chemical formula Fe 75-x Ni x Si 12.5 B 12.5 FeB, FeSi, pure Fe and Ni were weighed, where x was 2; that is, according to the atomic ratio of Fe, B, Si, and Ni of 73:12.5:12.5:2, FeB (of which B accounted for 19.37%), FeSi (of which Si accounted for 75%), pure Fe and Ni were weighed respectively, with a total mass of 20 g, and mixed to obtain a mixture.

[0050] S2. Place the mixture into an arc melting furnace and introduce argon gas into the furnace to create a protective atmosphere. Use arc discharge to generate high temperature to melt the mixture, and use magnetic stirring to fully mix the mixture. During the melting process, the front and back sides of the mixture are repeatedly melted three times, and each melting is accompanied by three magnetic stirring operations; after the melting is completed, the molten raw material is made into a φ6 cylindrical rod shape by arc melting and suction casting, and then naturally cooled to room temperature to obtain a Fe-Si-B based alloy doped with transition metals, which is recorded as Fe 73 Ni2Si 12.5 B 12.5 .

[0051] S3. The cooled Fe-Si-B alloy doped with transition metals was cut using a wire cutting machine to obtain small iron pieces with a thickness of 0.5 mm and a length and width of 5 mm. The pieces were then placed in a 2 mol / L KOH solution and subjected to dealloying corrosion treatment for 3 h to obtain a nanocatalyst, designated as NS-Fe 73 Ni2Si 12.5 B 12.5 .

[0052] Example 6 A method for preparing a nanocatalyst is the same as the method of Example 2, except that the Co atom in S1 is replaced by a Ni atom, comprising the following steps: S1, according to the chemical formula Fe 75-x Ni x Si 12.5 B 12.5 FeB, FeSi, pure Fe and Ni were weighed, where x was 5; that is, according to the atomic ratio of Fe, B, Si and Ni being 70:12.5:12.5:5, FeB (wherein B accounts for 19.37%), FeSi (wherein Si accounts for 75%), pure Fe and Ni were weighed respectively, with a total mass of 20 g, and mixed to obtain a mixture.

[0053] S2. Place the mixture into an arc melting furnace and introduce argon gas into the furnace to create a protective atmosphere. Use arc discharge to generate high temperature to melt the mixture, and use magnetic stirring to fully mix the mixture. During the melting process, the front and back sides of the mixture are repeatedly melted three times, and each melting is accompanied by three magnetic stirring operations; after the melting is completed, the molten raw material is made into a φ6 cylindrical rod shape by arc melting and suction casting, and then naturally cooled to room temperature to obtain a Fe-Si-B based alloy doped with transition metals, which is recorded as Fe 70 Ni5Si 12.5 B 12.5 .

[0054] S3. The cooled Fe-Si-B alloy doped with transition metals was cut using a wire cutting machine to obtain small iron pieces with a thickness of 0.5 mm and a length and width of 5 mm. The pieces were then placed in a 2 mol / L KOH solution and subjected to dealloying corrosion treatment for 3 h to obtain a nanocatalyst, designated as NS-Fe 70 Ni5Si 12.5 B 12.5 .

[0055] Example 7 A method for preparing a nanocatalyst is the same as the method of Example 3, except that the Co atom in S1 is replaced by a Ni atom, comprising the following steps: S1, according to the chemical formula Fe 75-x Ni x Si 12.5 B 12.5 FeB, FeSi, pure Fe and Ni were weighed, where x was 8; that is, according to the atomic ratio of Fe, B, Si, and Ni of 67:12.5:12.5:8, FeB (of which B accounted for 19.37%), FeSi (of which Si accounted for 75%), pure Fe and Ni were weighed respectively, with a total mass of 20 g, and mixed to obtain a mixture.

[0056] S2. Place the mixture into an arc melting furnace and introduce argon gas into the furnace to create a protective atmosphere. Use arc discharge to generate high temperature to melt the mixture, and use magnetic stirring to fully mix the mixture. During the melting process, the front and back sides of the mixture are repeatedly melted three times, and each melting is accompanied by three magnetic stirring operations; after the melting is completed, the molten raw material is made into a φ6 cylindrical rod shape by arc melting and suction casting, and then naturally cooled to room temperature to obtain a Fe-Si-B based alloy doped with transition metals, which is recorded as Fe 67 Ni8Si 12.5 B 12.5 .

[0057] S3. The cooled Fe-Si-B alloy doped with transition metals was cut using a wire cutting machine to obtain small iron pieces with a thickness of 0.5 mm and a length and width of 5 mm. The pieces were then placed in a 2 mol / L KOH solution and subjected to dealloying corrosion treatment for 3 h to obtain a nanocatalyst, designated as NS-Fe 67 Ni8Si 12.5 B 12.5 .

[0058] Example 8 A method for preparing a nanocatalyst is the same as the preparation method of Example 4, except that the Co atom in S1 is replaced by a Ni atom to obtain a nanocatalyst, which is recorded as NS-Fe 65 Ni10 Si 12.5 B 12.5 .

[0059] S1, according to the chemical formula Fe 75-x Ni x Si 12.5 B 12.5 FeB, FeSi, pure Fe and Ni were weighed, where x was 10; that is, according to the atomic ratio of Fe, B, Si and Ni of 65:12.5:12.5:10, FeB (of which B accounted for 19.37%), FeSi (of which Si accounted for 75%), pure Fe and Ni were weighed respectively, with a total mass of 20 g, and mixed to obtain a mixture.

[0060] S2. Place the mixture into an arc melting furnace and introduce argon gas into the furnace to create a protective atmosphere. Use arc discharge to generate high temperature to melt the mixture, and use magnetic stirring to fully mix the mixture. During the melting process, the front and back sides of the mixture are repeatedly melted three times, and each melting is accompanied by three magnetic stirring operations; after the melting is completed, the molten raw material is made into a φ6 cylindrical rod shape by arc melting and suction casting, and then naturally cooled to room temperature to obtain a Fe-Si-B based alloy doped with transition metals, which is recorded as Fe 65 Ni 10 Si 12.5 B 12.5 . .

[0061] S3. The cooled Fe-Si-B alloy doped with transition metals was cut using a wire cutting machine to obtain small iron pieces with a thickness of 0.5 mm and a length and width of 5 mm. The pieces were then placed in a 2 mol / L KOH solution and subjected to dealloying corrosion treatment for 3 h to obtain a nanocatalyst, designated as NS-Fe 65 Ni 10 Si 12.5 B 12.5 .

[0062] Comparative Example 1 A method for preparing a nanocatalyst comprises the following steps: S1, according to the chemical formula Fe 75 Si 12.5 B 12.5 FeB, FeSi and pure Fe were weighed; that is, according to the atomic ratio of 75:12.5:12.5, FeB (of which B accounts for 19.37%), FeSi (of which Si accounts for 75%) and pure Fe were weighed respectively, with a total mass of 20 g, and mixed to obtain a mixture.

[0063] S2. Place the mixture into an arc melting furnace and introduce argon gas into the furnace to create a protective atmosphere. Use arc discharge to generate high temperature to melt the mixture, and use magnetic stirring to fully mix the mixture. During the melting process, the front and back sides of the mixture are repeatedly melted three times, and each melting is accompanied by three magnetic stirring operations; after the melting is completed, the molten raw material is made into a φ6 cylindrical rod by arc melting and suction casting, and then naturally cooled to room temperature to obtain Fe 75 Si 12.5 B 12.5 .

[0064] S3, use wire cutting machine to cut the cooled Fe 75 Si 12.5 B 12.5 The iron sheet was cut to obtain a thickness of 0.5 mm and a length and width of 5 mm. It was then placed in a 2 mol / L KOH solution and subjected to dealloying corrosion for 3 h to obtain NS-Fe 75 Si 12.5 B 12.5 .

[0065] Depend on Figure 1 It is concluded that the red diamond peak represents NS-Fe 65 Co 10 Si 12.5 B 12.5 , the pink diamond peak represents Fe 65 Co 10 Si 12.5 B 12.5 , the blue diamond peak represents Fe 75 Si 12.5 B 12.5 Among them, 2 θ The peaks at angles of 44.675°, 65.026°, and 82.339° correspond to the (110), (200), and (211) crystal planes of Fe, respectively; θ The peaks at angles of 45.047°, 65.603°, and 79.730° correspond to the (210), (310), and (123) crystal planes of FeSi, respectively; θ The peaks at angles of 42.611°, 45.107°, 56.339° and 79.763° correspond to the (002), (211), (202) and (330) crystal planes of Fe2B, respectively. 75 Si 12.5 B 12.5 、Fe 65 Co 10 Si 12.5 B 12.5 and NS-Fe 65 Co 10Si 12.5 B 12.5 The diffraction peaks of Co7Fe3 are consistent with those of θ The peaks at angles of 45.169°, 65.712° and 83.252° are (110), (200) and (211), respectively, which proves that the prepared Fe 65 Co 10 Si 12.5 B 12.5 Containing four elements, Fe, Si, B, and Co, corresponding to the EDS spectrum, NS-Fe was successfully synthesized 65 Co 10 Si 12.5 B 12.5 .

[0066] Compared with Fe 75 Si 12.5 B 12.5 , NS-Fe 65 Co 10 Si 12.5 B 12.5 The diffraction intensity is stronger, indicating that Co doping can effectively improve the Fe 75 Si 12.5 B 12.5 The crystallinity of the Fe-Si phase is improved, especially the improvement of the crystallinity of the Fe-Si phase, which reflects the enhanced bonding between Si and metal. 65 Co 10 Si 12.5 B 12.5 , the Fe-Si phase disappears and the Fe phase appears, indicating that Si dissolves in the alkaline solution during the dealloying process. 65 Co 10 Si 12.5 B 12.5 In comparison, the intensity of the 42.611° diffraction peak weakened, indicating that part of the B element dissolved during the dealloying corrosion process.

[0067] The Fe 65 Co 10 Si 12.5 B 12.5 Surface morphology before and after dealloying. Figure 2 Figures a and b in the figure show that after corrosion, NS-Fe 65 Co 10 Si 12.5 B 12.5 A nano-sheet structure is formed on the surface, but some areas are not completely corroded. Figure 2 Figure c shows that compared with Fe without Co doping 75 Si12.5 B 12.5 ,See Figure 3 , the nanoporous structures on its surface are smaller and more numerous.

[0068] Depend on Figure 2 Figure d shows that the content distribution of the four elements Fe, Si, B, and Co is consistent with the results of the X-ray diffraction spectrum.

[0069] Depend on Figure 4 Figure a shows that NS-Fe 65 Co 10 Si 12.5 B 12.5 There are four elements, Fe, Co, Si, and B, on the surface of the quartz crystal, and their corresponding binding energy peaks are 787eV, 712eV, 180eV, and 102eV, respectively. Figure 4 The two peaks at 780.78eV and 795.98eV correspond to the 2p 3 / 2 and 2p 1 / 2 peaks; the two peaks near 785.18eV and 802.33eV correspond to Co 2+ Satellite peaks. 2+ The satellite peak intensity of the ion is close to the 2p 3 / 2 The intensity of NS-Fe 65 Co 10 Si 12.5 B 12.5 There is a large amount of +2 Co on the surface. Figure 4 Figure c shows that compared with NS-Fe 75 Si 12.5 B 12.5 , NS-Fe 65 Co 10 Si 12.5 B 12.5 A small amount of Fe still remains on the surface after dealloying 0 The characteristic peak of Co doping (706.03 eV) indicates that the valence state of Fe changes due to Co doping, and Fe atoms are less likely to be oxidized during the dealloying process.

[0070] Depend on Figure 4 The d in NS-Fe 65 Co 10 Si 12.5 B 12.5 The peak of the Si-metal bond on the surface is enhanced, indicating that Co doping helps the bonding between Si and metal. Figure 4 Figure e shows that the Si-O bond strength is enhanced while the Fe-O bond strength is weakened after Co doping, which is consistent with the results of Fe 2p and Si 2p.

[0071] Depend on Figure 5 As shown in Figure a, the overpotential of hydrogen evolution reaction decreases with the increase of Co doping amount. 65 Co 10 Si 12.5 B 12.5 Has the best hydrogen evolution reaction activity. NS-Fe 65 Co 10 Si 12.5 B 12.5 At 100mA / cm 2 The overpotential can reach 314.7mV at a current density of 1000 nm, which is much lower than that of NS-Fe 67 Co8Si 12.5 B 12.5 (348.7mV), NS-Fe 70 Co5Si 12.5 B 12.5 (395.7mV) and NS-Fe 73 Co2Si 12.5 B 12.5 (415.7mV). Similarly, NS-Fe 65 Co 10 Si 12.5 B 12.5 At 10 mA / cm 2 The overpotential at a current density of 175.1 mV is due to the synergistic effect between Fe and Co ions. During the H2 evolution process of water electrolysis, the Co atoms in these Co-Fe serve as the reaction sites for the cleavage of the OH bonds of water, while the Fe atoms can serve as the H2 evolution center. Moreover, the surface after corrosion has the largest specific surface area, which can expose more active sites and present better hydrogen evolution reaction performance. Figure 5 Figure b shows that Co-doped NS-Fe 75 Si 12.5 B 12.5 Significantly higher than undoped NS-Fe 75 Si 12.5 B 12.5 The performance is greatly improved. Uncorroded Fe 65 Co 10 Si 12.5 B 12.5 With NS-Fe 75 Si 12.5 B 12.5 The performance is similar to that of the 2 Under the current density of 65 Co 10 Si 12.5 B 12.5 Better performance. Figure 5 Figure c shows that at a current density of 10 mA / cm 2 Next, NS-Fe 67 Co8Si 12.5 B 12.5 NS-Fe 70 Co5Si 12.5 B 12.5 NS-Fe 73 Co2Si 12.5 B 12.5 、Fe 65 Co 10 Si 12.5 B 12.5 NS-Fe 75 Si 12.5 B 12.5 The overpotentials are 198.2mV, 211.1mV, 199.7mV, 215mV, and 214mV respectively.

[0072] In order to further study the effect of Co doping on NS-Fe 75 Si 12.5 B 12.5 The influence of Tafel analysis will reveal the kinetics and reaction mechanism of hydrogen evolution reaction. Figure 5 As shown in Figure d, NS-Fe 65 Co 10 Si 12.5 B 12.5 NS-Fe 67 Co8Si 12.5 B 12.5 NS-Fe 70 Co5Si 12.5 B 12.5 NS-Fe 73 Co2Si 12.5 B 12.5 、Fe 65 Co 10 Si 12.5 B 12.5 The Tafel slopes of NS-Fe were 134mV / dec, 165mV / dec, 212mV / dec, 161mV / dec, and 210mV / dec, respectively. These results indicate that 65 Co 10 Si 12.5 B 12.5 It is more conducive to improving the catalytic kinetic performance of hydrogen evolution reaction.

[0073] Depend on Figure 5 The e diagram in the figure shows that NS-Fe 60 Co 10 Si12.5 B 12.5 The charge transfer resistance is the smallest, 2.265Ω, which is smaller than NS-Fe 67 Co8Si 12.5 B 12.5 (2.709Ω), NS-Fe 70 Co5Si 12.5 B 12.5 (2.961Ω), NS-Fe 73 Co2Si 12.5 B 12.5 (2.843Ω)、Fe 60 Co 10 Si 12.5 B 12.5 (2.713Ω) and NS-Fe 75 Si 12.5 B 12.5 (3.67Ω). This indicates that during the hydrogen evolution reaction, NS-Fe 65 Co 10 Si 12.5 B 12.5 The enhanced electron transfer rate confirms that Co doping has superior electrocatalytic performance.

[0074] By obtaining the area of the cyclic voltammetry characteristic curve at different rates in the non-Faraday region and the slope of the scan rate fitting line, the double layer specific capacitance of different materials can be obtained. C dl .like Figure 5 As shown in figure f, in 1 mol / L KOH solution, when the voltage is 0.05 V, the linear relationship between the current density difference and the scan rate is obtained. 65 Co 10 Si 12.5 B 12.5 NS-Fe 67 Co8Si 12.5 B 12.5 NS-Fe 70 Co5Si 12.5 B 12.5 NS-Fe 73 Co2Si 12.5 B 12.5 、Fe 65 Co 10 Si 12.5 B 12.5 The Cdl values (corresponding ECSA values) are 0.342mF / cm (8.55), 0.325mF / cm (8.125), 0.283mF / cm (7.075), 0.258mF / cm (6.45), and 0.157mF / cm (3.925), respectively.C dl The ECSA values gradually increase with increasing Co doping levels. This is because Co doping improves the dispersion of the nanocatalyst, making the nanocatalyst particles smaller and having a larger specific surface area. Furthermore, Co doping can induce an electronic effect, changing the electronic state of the FeSiB alloy and thus affecting its catalytic performance. Furthermore, the synergistic effect between Co and Fe, Si, and B leads to the formation of new active sites, increasing the electrochemical active area.

[0075] In addition, NS-Fe 65 Co 10 Si 12.5 B 12.5 It also exhibits excellent stability in hydrogen evolution reaction. Figure 6 Figure a shows that after 1000 cycles, NS-Fe 65 Co 10 Si 12.5 B 12.5 The linear sweep voltammetric characteristic curve has no significant change compared to that before cycling, indicating that the stability of the hydrogen evolution reaction is good. Figure 6 Figure b shows that after 15 hours of hydrogen evolution reaction, the current density of hydrogen evolution reaction decreased to 81.9% of the initial value, indicating that the NS-Fe 65 Co 10 Si 12.5 B 12.5 It can carry out hydrogen evolution reaction stably for a long time. Co doping improves NS-Fe 75 Si 12.5 B 12.5 The crystallinity of the nanocatalyst is enhanced, the bonding of metal bonds is strengthened, and the lattice structure of the nanocatalyst is improved, which not only enhances the catalytic performance of the nanocatalyst, but also enhances its stability.

[0076] like Figure 7 As shown, the green diamond peak represents NS-Fe 73 Ni2Si 12.5 B 12.5 , the deep red diamond peak represents Fe 73 Ni2Si 12.5 B 12.5 , the light blue diamond peak represents Fe 75 Si 12.5 B 12.5 Samples. Among them, 2 θ =45.22°, 65.38°, and 83.1°, which correspond to Fe 0.95 Ni 0.05 (PDF#04-004-8515) and Fe (PDF#04-004-8514) (110), (200) and (211) planes, 2 θ The diffraction peaks of =42.527°, 45.043°, 49.71°, 50.436°, 56.244°, 56.912°, 79.533°, and 80.668° correspond to the (002), (121), (112), (022), (130), (132), (330), and (141) crystal planes of Fe2B (PDF#36-1332), respectively. θ The diffraction peaks at 45.047°, 65.603° and 79.730° correspond to the (210), (310) and (123) crystal planes of FeSi (PDF#86-0792), respectively. 75 Si 12.5 B 12.5 、Fe 73 Ni2Si 12.5 B 12.5 and NS-Fe 73 Ni2Si 12.5 B 12.5 The diffraction peaks of NS-Fe 73 Ni2Si 12.5 B 12.5 There are four elements in it: Fe, Ni, B, and Si.

[0077] Compared with Fe 75 Si 12.5 B 12.5 , NS-Fe 73 Ni2Si 12.5 B 12.5 The diffraction intensity of NS-Fe after dealloying is stronger, indicating that doping with Ni can effectively improve the crystallinity of the material. In particular, the improvement of the crystallinity of the Fe-Si phase is due to the enhanced bonding between Si and metal. 73 Ni2Si 12.5 B 12.5 The Fe-Si phase disappears and the Fe phase appears, indicating that Si dissolves in the alkaline solution during the dealloying process. Compared to the uncorroded sample, the intensity of the 42.611° diffraction peak decreases, indicating that some B elements dissolve during the dealloying corrosion process. During the corrosion process, the active components Si and B, as well as some Fe atoms, dissolve at the electrolyte interface, forming vacancies. This causes Ni to undergo surface migration and recombination, redistributing the electron density and forming a stronger electronic structure between Ni and Fe. This optimizes the adsorption and desorption of intermediates during the reaction, thereby enhancing the activity of the hydrogen evolution reaction.

[0078] from Figure 8 Figures a and b in the figure show that after corrosion, NS-Fe 73 Ni2Si 12.5B 12.5 A nanosheet-like structure is formed on the surface, but some areas are not completely corroded. Figure 8 Figure c shows that compared with NS-Fe without Ni doping 75 Si 12.5 B 12.5 , the nanoporous structures on its surface are smaller and more numerous. Figure 8 Figures d and e show the number and size of the layers inside the hole.

[0079] Depend on Figure 8 The f diagram in the figure shows that NS-Fe 73 Ni2Si 12.5 B 12.5 The content distribution of the four elements Fe, Ni, Si and B is consistent with the results of X-ray diffraction spectrum.

[0080] Depend on Figure 9 Figure a shows the presence of Fe, Ni, Si, B, C and O elements and the absence of other elements, which confirms that the purity of the nanocatalyst preparation is at a high level. Figure 9 As shown in b, a binding energy peak signal was found, indicating that Ni element was successfully doped into NS-Fe 75 Si 12.5 B 12.5 Observation Figure 9 Figure c shows that compared with NS-Fe 75 Si 12.5 B 12.5 , NS-Fe 73 Ni2Si 12.5 B 12.5 A small amount of Fe still remains on the surface after dealloying 0 The characteristic peak (706.13 eV) indicates that Ni doping changes the valence state of Fe, and Fe atoms are less likely to be oxidized during the dealloying process. Figure 9 The d figure in the figure shows that compared with NS-Fe 75 Si 12.5 B 12.5 and NS-Fe 73 Ni2Si 12.5 B 12.5 X-ray photoelectron spectroscopy of Si 2p, NS-Fe 73 Ni2Si 12.5 B 12.5 The peak intensity of the Si-metal bond on the surface is enhanced, indicating that Ni doping helps the bonding between Si and metal. Figure 9Figure e shows that after Ni doping, the Si-O bond strength and Fe-O bond strength are weakened, and the Fe-OH bond is gradually enhanced after Ni doping, which is conducive to the combination of Fe and OH. The generated FeOOH enhances the catalytic activity of the nanocatalyst.

[0081] Depend on Figure 10 Figure a shows that Fe 73 Ni2Si 12.5 B 12.5 The performance is the best at a current density of 10mA / cm 2 The hydrogen evolution overpotential under the condition of NiO2 is reduced to 168 mV, indicating that Ni doping can enhance the interaction between electrons. However, a higher Ni content will hinder the adsorption and dissociation of hydrogen ions. Figure 10 From Figure b, we can see that Fe 73 Ni2Si 12.5 B 12.5 with Fe 75 Si 12.5 B 12.5 Compared with the previous results, the voltage has increased by 35.4 mV. This is because the introduction of cationic Ni by doping can induce the redistribution of electron density, accurately control the electronic structure of Fe-Ni, optimize the adsorption and dissociation of intermediates in the reaction, and thus improve the catalytic activity of the nanocatalyst hydrogen evolution reaction. 73 Ni2Si 12.5 B 12.5 with Fe 73 Ni2Si 12.5 B 12.5 In comparison, the dealloying corrosion performance is improved by 55mV. This is because the dealloying and gold corrosion form a nanoporous structure on the surface of the nanocatalyst, which can expose more active sites, increase the electrochemical surface area, and present better hydrogen evolution reaction performance.

[0082] It is found from Figure c in 9 that NS-Fe 75 Si 12.5 B 12.5 The overpotential of NS-Fe 65 Ni 10 Si 12.5 B 12.5 Not much different. Figure 10 Figure d shows that NS-Fe 73 Ni2Si 12.5 B 12.5 The Tafel slope is only 158mV / dec, which is much lower than that of NS-Fe 70 Ni5Si 12.5 B 12.5 (182), NS-Fe 67 Ni8Si 12.5 B 12.5(198), NS-Fe 65 Ni 10 Si 12.5 B 12.5 (205) Fe 73 Ni2Si 12.5 B 12.5 (175) is lower, indicating that the smaller the Tafel slope, the faster the electron transfer and catalytic reaction kinetics. 73 Ni2Si 12.5 B 12.5 Able to reduce hydrogen ions at lower overpotential values. Figure 10 The e diagram in the figure shows that NS-Fe 73 Ni2Si 12.5 B 12.5 NS-Fe 70 Ni5Si 12.5 B 12.5 NS-Fe 67 Ni8Si 12.5 B 12.5 NS-Fe 65 Ni 10 Si 12.5 B 12.5 、Fe 73 Ni2Si 12.5 B 12.5 and NS-Fe 75 Si 12.5 B 12.5 The charge transfer resistances are approximately 2.515Ω, 2.537Ω, 3.172Ω, 3.406Ω, 2.578Ω and 3.67Ω, respectively. 73 Ni2Si 12.5 B 12.5 The charge transfer resistance is small (2.515Ω), indicating that Ni and Fe have a strong synergistic effect on improving electrical conductivity, which is beneficial to rapid electron transfer and improves the performance of hydrogen evolution reaction.

[0083] Depend on Figure 10 The f graph in C dl Figure, NS-Fe 73 Ni2Si 12.5 B 12.5 of C dl The value is 0.279mF / cm, which is significantly larger than NS-Fe 70 Ni5Si 12.5 B 12.5 (0.140mF / cm), NS-Fe 67 Ni8Si 12.5 B 12.5(0.106mF / cm), NS-Fe 65 Ni 10 Si 12.5 B 12.5 (0.077mF / cm) and Fe 73 Ni2Si 12.5 B 12.5 (0.136mF / cm), indicating that the doping and corrosion process make NS-Fe 73 Ni2Si 12.5 B 12.5 It has abundant surface catalytic active sites. According to the formula ECSA= C dl / C s , NS-Fe 73 Ni2Si 12.5 B 12.5的 The ECSA value is calculated to be 6.975 cm 2 This is attributed to the synergistic effect between interfacial charge redistribution and Ni-Fe, which can enhance the contact area with the electrolyte, thereby improving the charge transfer ability at the interface and promoting mass transfer between reactants and products.

[0084] At the same time, chronopotentiometry was used to evaluate the 73 Ni2Si 12.5 B 12.5 Long-term stability in 1 mol / L KOH solution. Figure 11 As shown in Figure a, after 1000 cycles, NS-Fe 73 Ni2Si 12.5 B 12.5 The linear sweep voltammetric characteristic curve has no significant change compared to that before cycling, indicating that the stability of the hydrogen evolution reaction is good. Figure 11 As shown in Figure b, after 20 hours of hydrogen evolution reaction, the current density of the hydrogen evolution reaction decreased to 86% of the initial value, indicating that the hydrogen evolution reaction can be carried out stably for a long time.

[0085] Co-doped NS-Fe 75 Si 12.5 B 12.5 , making the nanocatalyst particles smaller and larger in specific surface area. Co doping can cause electronic effects and change the NS-Fe 75 Si 12.5 B 12.5 The electronic state of Ni-doped NS-Fe can be changed, thereby affecting its catalytic performance. In addition, the synergistic effect between Co and Fe, Si and B can also lead to the formation of new active sites and increase the electrochemical active area. 75 Si 12.5 B 12.5It is beneficial to the improvement of hydrogen evolution reaction performance, which is attributed to the synergistic effect between interfacial charge redistribution and Ni-Fe, which can enhance the contact area with the electrolyte, thereby improving the charge transfer ability at the interface and promoting mass transfer between reactants and products.

[0086] It should be noted that when the present invention involves a numerical range, it should be understood that the two endpoints of each numerical range and any numerical value between the two endpoints can be selected. Since the steps and methods used are the same as those in the embodiment, in order to avoid redundancy, the present invention describes a preferred embodiment.

[0087] Although the preferred embodiments of the present invention have been described, those skilled in the art will be able to make additional changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

Claims

1. A nanocatalyst, characterized in that: The nanocatalyst is a Fe-Si-B based alloy doped with transition metals, and its general chemical formula is Fe 75-x M x Si 12.5 B 12.5 , and x is 2~10; Wherein, M is selected from transition metals Co or Ni.

2. The nanocatalyst according to claim 1, characterized in that The surface of the nanocatalyst has a lamellar structure.

3. The nanocatalyst according to claim 1, characterized in that When M is transition metal Co, the nanocatalyst is Fe 73 Co2Si 12.5 B 12.5 、Fe 70 Co5Si 12.5 B 12.5 、Fe 67 Co8Si 12.5 B 12.5 or Fe 65 Co 10 Si 12.5 B 12.5 .

4. The nanocatalyst according to claim 1, characterized in that When M is transition metal Ni, the nanocatalyst is Fe 73 Ni2Si 12.5 B 12.5 、Fe 70 Ni5Si 12.5 B 12.5 、Fe 67 Ni8Si 12.5 B 12.5 or Fe 65 Ni 10 Si 12.5 B 12.5 .

5. A method for preparing the nanocatalyst according to claim 1, characterized in that: The following steps are involved: The general chemical formula is Fe 75-x M x Si 12.5 B 12.5 , M is a transition metal Co or Ni, FeB, FeSi and Fe, and Co or Ni are weighed and mixed to obtain a mixture; wherein x is 2 to 10; The mixed material is smelted to obtain a Fe-Si-B based alloy doped with a transition metal; The Fe-Si-B based alloy doped with transition metals is subjected to dealloying corrosion treatment to corrode away Si atoms and part of B atoms on the surface of the Fe-Si-B based alloy doped with transition metals, so that the surface presents a lamellar structure, thereby obtaining a nanocatalyst.

6. The method for preparing a nanocatalyst according to claim 5, characterized in that: The conditions for dealloying corrosion treatment are: corrosion in a strong alkaline solution of 0.5 mol / L~4 mol / L for 2h~3h.

7. The method for preparing a nanocatalyst according to claim 6, wherein: The strong alkaline solution is selected from KOH solution or NaOH solution.

8. The method for preparing a nanocatalyst according to claim 5, wherein: The smelting treatment conditions are: smelting at 1800°C~2200°C for 5min~10min.

9. Use of the nanocatalyst according to claim 1 in preparing a catalyst for hydrogen evolution reaction by electrolysis of water.

Citation Information

Patent Citations

  • Preparation method of lanthanum-doped iron-cobalt-base soft magnetic material

    CN104593666A

  • R-(Fe, Co)-B sintered magnet and making method

    CN106710766A

  • A process for producing a tetrahydrofuran compound comprising at least two amine functional groups

    CN110325520A

  • Nanocrystalline magnetically soft alloy and preparation method and application thereof

    CN118053644A

  • Preparation method and application of nitrogen-containing iron-based soft magnetic amorphous / nanocrystalline alloy

    CN118957455A